The Rookie - Eastwood, Clint; Eastwood, Clint; Charlie Sheen; Raul Julia; Sonia Braga; Tom Skerritt; Lara Flynn Boyle; Pepe Serna; Marco Rodríguez; Pete Randall; Donna Mitchell; Xander Berkeley; et al. (USA Kazanjian/Siebert Productions, 1990)
Clint Eastwood plays a veteran cop who gets stuck with a rookie cop (Charlie Sheen) to chase down a German criminal (Raul Julia.)
Languages : English, Spanish
Subtitles : English, Spanish, Italian, Turkish, Slovenian
Keywords: Action; Comedy; Thriller